EKSPLORASI MURKA ALLAH: MURKA ALLAH TERHADAP MIRYAM SEBAGAI EKSPRESI KEADILAN ILAHI DALAM BILANGAN 12:9 - Tanasyah, Yusak; Akimas , Handreas Sudarmiko; Yensi, Yensi (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
This study examines the theology of God's wrath as expressed in Numbers 12:9, focusing on textual and contextual analysis. The verse describes God's response to Miriam and Aaron's actions in questioning the authority of Moses, God's chosen leader for the Israelites. Using a hermeneutic approach, this study explores the historical, social, and theological background of the event. The findings of the study indicate that God's wrath in Numbers 12:9 is not only an expression of anger but also a disciplinary action that aims to teach and correct His people. God's wrath reflects His justice and holiness and reinforces the importance of obedience and respect for God's established authority. The historical context shows that Miriam and Aaron's actions are a form of rebellion against the divine order that results in serious consequences. This study concludes that God's wrath in Numbers 12:9 functions as a teaching and corrective mechanism that aims to maintain the loyalty and obedience of the Israelites to God. This understanding provides deeper insight into the nature of God's wrath in Old Testament theology, namely as a manifestation of God's love, justice, and desire to guide His people towards righteousness